A quality model of OpenCourseWare applied to Engineering courses - Piedra Pullaguari, N. (2010)
The OpenCourseWare (OCW) project started at the Massachusetts Institute of Technology (MIT), in the year 2001, with the aim of offering pedagogical materials in an open and free of charge basis to society. The main objective of this proposal is to promote and develop higher education sharing, in a free and consistent way. The teaching resources with other educators who may re-use them for their teaching work; students; graduates and anyone in general who wants to improve its knowledge.This philosophy is being spread to the world main universities creating the OCW Consortium (OCWC), in which more than 250 Universities and Institutions collaborate. Within this context new proposals, both technical and philosophical are arising for the freely disposal of teaching resources. Universia, the Latin-American Universities net, gather at present about 1070 universities from 11 different countries. Among its goals are: the offer of many quality services to the university community, supporting teaching and scientific research projects, encouraging the use of new technologies and promoting the business - university relationship, in order to encourage a Latin-American site for knowledge The initial conditions to include Higher Educational Institutions in this project regard three different types: educational, technical and legal matters. For the first one, it is demanded the publication of teaching materials orderly structured with at least 10 courses. Within these materials, it can be included all kind of resources: presentations, books, videos, simulations programs, etc. always with a common organization and appearances. Regarding technical demands a globally and approachable site via Internet with the right quality must be maintained. Although it has not been a requirement, most of participants have used the technology of content management based on eduCommons, an Open Source project developed by Utah State University, which include very important normalized, flexible and personalized features. Finally, the legal aspects came from the Creative Commons License that implies to offer and publish copyright cleared materials. The use, re-use and adaptation are allowed, provided the author of material is mentioned; they are not used with commercial purposes and they are offered, at least, within the same sharing conditions. The OCW Universia project provides member institutions with technical assistance, through Technical office of the UPM, for setting up the management and publication platform for its subjects, which constitutes the OCW site for each University. In the current situation, with a growing number of coursespubliched, quality of materials becomes as the critical priority. This paper proposes a quality model. This model has been elaborated from an initial survey among Offices of the OCW UNIVERSA Consortium. Later, this model has been applied to determine which courses of Engineering have been better evaluated. © American Society for Engineering Education, 2010.